TRANSPARENCY AS A PILLAR OF GOOD CORPORATE GOVERNANCE: A LITERATURE STUDY ON FINANCIAL MANAGEMENT AND PERFORMANCE OF REGIONAL-OWNED ENTERPRISES (BUMDS) - Tegor, Tegor; Siswanto, Dwi Joko; Azmi, Azmi; Thasimmim, Said Nuwrun (Pena Cendekia Insani, 2025)
This research examines transparency issues in the financial report management of Regional-Owned Enterprises (BUMD) in Karimun Regency through a literature study approach. The research shows that BUMDs in Karimun Regency experienced a total absence of annual financial report publications in the 2023-2024 period, reflecting a serious deficit in accountability and governance. Analysis from various credible sources, including SINTA-indexed journal articles and institutional reports, identifies several main factors causing weak transparency, including: low commitment to implementing Good Corporate Governance principles, civil servant concurrent position practices that create conflicts of interest, and gaps between regulations and their implementation in the field. The research findings show that this absence of transparency has serious implications for the lack of public accountability, high risk of authority abuse, weakened oversight, and hindered achievement of BUMD objectives to contribute to the regional economy. The research recommends strengthening political commitment from local governments, optimizing the supervisory function of the Regional Parliament (DPRD), comprehensive implementation of Good Corporate Governance principles by BUMD management, utilization of information technology for report publication, and increasing the active role of civil society in public oversight.